Lower extremity function in patients with early rheumatoid arthritis during the first five years, and relation to other disease parameters. (3rd September 2019) - Mellblom Bengtsson, M; Hagel, S; Jacobsson, LTH; Turesson, C
Abstract : Objective : The objective of this study was to investigate lower extremity function in early rheumatoid arthritis (RA) and assess its relation to other disease parameters. Methods : An inception cohort (recruited in 1995–2005) of patients with early RA was followed according to a structured protocol. Lower extremity function was investigated at inclusion and after 1, 2, and 5 years using the Index of Muscle Function (IMF; total score 0–40). Self-reported disability was estimated using the Health Assessment Questionnaire (HAQ). The same rheumatologist assessed patients for swollen joints and joint tenderness. Results : In total, 106 patients were included. Lower extremity function improved from baseline to the 1 year visit [IMF total median 10, interquartile range (IQR) 4–16 vs 7, IQR 3–12; p = 0.01]. This was followed by a decline in lower extremity function. Throughout the study, there were significant correlations between IMF and HAQ scores (r = 0.38–0.58; p < 0.001 at all time-points). Patients with knee and/or ankle synovitis at inclusion had significantly higher IMF scores than those without such joint involvement, with similar associations for joint tenderness. In multivariate linear regression analysis, ankle synovitis was significantly associated with higher IMF scores (β = 2.91, 95% confidence interval 0.28–5.54), whereas there was no such association for metatarsophalangeal (MTP) arthritis. Conclusion : Lower extremity function in early RA improved during the first year, followed by a gradual decline. Ankle involvement had a greater impact than MTP involvement on lower extremity function. This highlights the importance of treating large-joint disease in RA.